Pengembangan Video Animasi Berbasis Canva Pada Pembelajaran IPAS Kelas III MIN 2 Dharmasraya - Estuhono, Estuhono; Ahmad Ilham Asmaryadi Ma; Muhammad Karles (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research aims to develop Canva-based animation videos for learning science and science class III Min 2 Dharmasraya. This research uses the type of research and development. The research and development model used uses 4D developed by S. Thigharajan, Doroty Semmel, and Melvyn I. Semmel. This development stage is: Define, Design, Develop, Disseminate. The type of data taken in this research is primary data, namely data taken from the results of validation of teaching materials. The development of the instruments used in this research used validity, practicality and effectiveness instruments. Data collection techniques used were observation, interviews, questionnaires. The data analysis technique used uses validity, practicality and effectiveness data analysis. Based on the validation results of video media, which was assessed by 3 validators, it shows that video media obtained an average percentage of 82.76% with a very valid category, so it can be said that this video media is suitable for use by students. The practicality of video media was assessed from a questionnaire on the responses of educators and students to video learning media, totaling 1 educator and student of class III MIN 2 Dharmasraya, namely those who obtained a percentage of 95.5% in the very practical category. The effectiveness of the learning video media as assessed by the results of the test scores given to students in the form of objective questions totaling 20 questions obtained a percentage of 93.1% in the very effective category so it can be said that the effective use of this learning video media is able to increase the value of students' learning outcomes.